Frontal theta reveals further information about neural valence‐dependent processing of augmented feedback in extensive motor practice—A secondary analysis - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (European Journal of Neuroscience)
Abstract Supplementing an earlier analysis of event‐related potentials in extensive motor learning (Margraf et al., 2022a, 2022b), frontal theta‐band activity (4–8 Hz) was scrutinized. Thirty‐seven participants learned a sequential arm movement with 192 trials in each of five practice sessions. Feedback, based on a performance adaptive bandwidth, was given after every trial. Electroencephalogram (EEG) was recorded in the first and last practice sessions. The degree of motor automatization was tested under dual‐task conditions in a pre‐test–post‐test design. Quantitative error information was transported in both feedback conditions (positive and negative). Frontal theta activity was discussed as a general signal that cognitive control is needed and, therefore, was expected to be higher after negative feedback. Extensive motor practice promotes automatization, and therefore, decreased frontal theta activity was expected in the later practice. Further, it was expected that frontal theta was predictive for subsequent behavioural adaptations and the amount of motor automatization. As the results show, induced frontal theta power was higher after negative feedback and decreased after five sessions of practice. Moreover, induced theta activity was predictive for error correction and, therefore, an indicator of whether the recruited cognitive resources successfully induced behavioural adaptations. It remains to be solved why these effects, which fit well with the theoretical assumptions, were only revealed by the induced part of frontal theta activity. Further, the amount of theta activity during practice was not predictive for the degree of motor automatization. It seems that there might be a dissociation between attentional resources associated with feedback processing and attentional resources associated with motor control.
Keywords: General Neuroscience

Protein intake and type 2 diabetes mellitus: an umbrella review of systematic reviews for the evidence-based guideline for protein intake of the German Nutrition Society - Schulze, Matthias B.; Haardt, Julia; Amini, Anna M.; Kalotai, Nicole; Lehmann, Andreas; Schmidt, Annemarie; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Kühn, Tilman; Louis, Sandrine; et al. (European Journal of Nutrition)
Abstract Purpose Protein-rich foods show heterogeneous associations with the risk of type 2 diabetes (T2D) and it remains unclear whether habitual protein intake is related to T2D risk. We carried out an umbrella review of systematic reviews (SR) of randomised trials and/or cohort studies on protein intake in relation to risks of T2D. Methods Following a pre-specified protocol (PROSPERO: CRD42018082395), we retrieved SRs on protein intake and T2D risk published between July 1st 2009 and May 22nd 2022, and assessed the methodological quality and outcome-specific certainty of the evidence using a modified version of AMSTAR 2 and NutriGrade, respectively. The overall certainty of evidence was rated according to predefined criteria. Results Eight SRs were identified of which six contained meta-analyses. The majority of SRs on total protein intake had moderate or high methodological quality and moderate outcome-specific certainty of evidence according to NutriGrade, however, the latter was low for the majority of SRs on animal and plant protein. Six of the eight SRs reported risk increases with both total and animal protein. According to one SR, total protein intake in studies was ~ 21 energy percentage (%E) in the highest intake category and 15%E in the lowest intake category. Relative Risks comparing high versus low intake in most recent SRs ranged from 1.09 (two SRs, 95% CIs 1.02–1.15 and 1.06–1.13) to 1.11 (1.05–1.16) for total protein (between 8 and 12 cohort studies included) and from 1.13 (1.08–1.19) to 1.19 (two SRs, 1.11–1.28 and 1.11–1.28) (8–9 cohort studies) for animal protein. However, SRs on RCTs examining major glycaemic traits (HbA 1c , fasting glucose, fasting insulin) do not support a clear biological link with T2D risk. For plant protein, some recent SRs pointed towards risk decreases and non-linear associations, however, the majority did not support an association with T2D risk. Conclusion Higher total protein intake was possibly associated with higher T2D risk, while there is insufficient evidence for a risk increase with higher intakes of animal protein and a risk decrease with plant protein intake. Given that most SRs on plant protein did not indicate an association, there is possibly a lack of an effect.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Lydia Böttger (Universität Paderborn) rezensiert: Burwitz-Melzer, Eva; Riemer, Claudia; Schmelter, Lars (Hrsg.) (2022): Feedback beim Lehren und Lernen von Fremd- und Zweitsprachen. Arbeitspapiere der 42. Frühjahrs- konferenz zur Erforschung des Fremdsprachenunterrichts. [Giessener Beiträge zur Fremdsprachendidaktik]. Tübingen: Narr Francke Attempto, 245 Seiten. ISBN 978-3- 8233-8569-1 - Böttger, Lydia (www.daz-portal.de)

Alignment between timing of ‘highest caloric intake’ and chronotype in relation to body composition during adolescence: the DONALD Study - Jankovic, Nicole; Schmitting, Sarah; Stutz, Bianca; Krüger, Bettina; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)
Abstract Purpose Our aim was to assess alignment in timing of ‘highest caloric intake’ with individual chronotype and its association with body composition in adolescents. Methods We used repeatedly collected data from n = 196 adolescents (age 9–16 years, providing N = 401 yearly questionnaires) of the DONALD open cohort study. Chronotype was assessed by the Munich Chronotype Questionnaire from which midpoint of sleep (MSFsc) was derived. A sex- and age-specific diet-chrono-alignment score (DCAS) was calculated as the difference in hours between the chronotype-specific median timing of highest caloric intake of the studied population and the individual timing of ‘highest caloric intake’ or vice versa. Repeated-measures regression models were applied to study cross-sectional and longitudinal associations between the DCAS and body composition, e.g., Fat Mass Index (FMI) or Fat Free Mass Index (FFMI). Results DCAS ranged from −6:42 h to + 8:01 h and was not associated with body composition. Among adolescents with a later chronotype ( N = 201) a 1 h increase in DCAS (later consumption of ‘highest caloric intake’ in comparison to the median intake of that group), increased FFMI by 1.92 kg/m 2 (95% CI: 0.15, 3.69, p value = 0.04) over a median follow-up of 0.94 year. Conclusion Alignment of energy intake with individual chronotype appears beneficial for FFMI among those with a late chronotype.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Neuartiger Ansatz zum Richten von zwei- und dreidimensionalen Fehlern an einem Federdraht - Bathelt, Lukas; Djakow, Eugen; Dahms, Frederik; Henke, Christian; Trächtler, Ansgar; Homberg, Werner (Ilmenauer Federntag 2023: Neueste Erkenntnisse zu Funktion, Berechnung, Prüfung und Gestaltung von Federn und Werkstoffen)

Reviewing from a Distance: Uncovering Asymmetric Moderations of Spatial and Temporal Distances Between Sentiment Negativity and Rating - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis (MIS Quarterly)

Transmission electron microscopy and transdisciplinary research - Bürger, Julius; Lindner, Jörg K. N. (Climate Protection, Resource Efficiency, and Sustainable Mobility - Transdisciplinary Approaches to Design and Manufacturing Technology)

Transmission electron microscopy and transdisciplinary research - Bürger, Julius; Lindner, Jörg K. N. (Climate Protection, Resource Efficiency, and Sustainable Mobility - Transdisciplinary Approaches to Design and Manufacturing Technology)

Transmission electron microscopy and transdisciplinary research - Bürger, Julius; Lindner, Jörg K. N. (Climate Protection, Resource Efficiency, and Sustainable Mobility - Transdisciplinary Approaches to Design and Manufacturing Technology)

A Comparison of the Most Intense Periods (MIPs) During Competitive Matches and Training Over an 8-Week Period in a Male Elite Field Hockey Team - Büchel, Daniel; Döring, Michael; Baumeister, Jochen (Journal of Science in Sport and Exercise)
Abstract Purpose Wearables serve to quantify the on-court activity in intermittent sports such as field hockey (FH). Based on objective data, benchmarks can be determined to tailor training intensity and volume. Next to average and accumulated values, the most intense periods (MIPs) during competitive FH matches are of special interest, since these quantify the peak intensities players experience throughout the intermittent matches. The aim of this study was to retrospectively compare peak intensities between training and competition sessions in a male FH team competing in the first german division. Methods Throughout an 8-week in-season period, 372 individual activity datasets (144 datasets from competitive sessions) were recorded using the Polar Team Pro sensor (Kempele, Finland). MIPs were calculated applying a rolling window approach with predefined window length (1–5 min) and calculated for Total distance, High-Intensity-Running distance (> 16 km/h), Sprinting distance (> 20 km/h) and Acceleration load. Significant differences between training and competition MIPs were analysed through non-parametric statistical tests ( P < 0.05). Results Analyses revealed higher MIPs during competition for all considered outcomes ( P < 0.001). Effect size estimation revealed strongest effects for sprinting distance ( d = 1.89 to d = 1.22) and lowest effect sizes for acceleration load ( d = 0.92 to d = 0.49). Conclusion The present findings demonstrate that peak intensities during training do not reach those experienced during competitive sessions in a male FH team. Training routines such as manipulations of court-dimensions and team sizes might contribute to this discrepancy. Coaches should compare training and competition intensities to recalibrate training routines to optimize athletes’ preparation for competition.
Keywords: Nutrition and Dietetics; Rehabilitation; Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; Physiology

Riegel, Ulrich / Zimmermann, Mirjam (2022). Evaluation des konfessionell-kooperativen Religionsunterrichts in Nordrhein-Westfalen. Stuttgart: Kohlhammer. ISBN 978-3-17-043134-8. 333 Seiten. - Hüster, Jonas Maximilian (Religionspädagogische Beiträge)
Keywords: Religious studies; Education

"Wir machen dann das, worauf wir Bock haben" - Eine empirische Analyse zur Bedeutung fachdidaktischer Überzeugungen für die unterrichtsbezogene Lehrerkooperation - Engemann, Mario

Schreiben als Wissensproduktion? Eine Mikroanalyse der Vielstimmigkeit akademischer Selbstbildung und Enkulturation - Karsten, Andrea (Bedingungen der Wissensproduktion. Qualifizierung, Selbstoptimierung und Prekarisierung in Wissenschaft und Hochschule)

Characterization of Various Environmental Influences on the Inductive Localization - Lange, Sven; Hilleringmann, Ulrich; Hedayat, Christian; Kuhn, Harald; Förstner, Jens (2023 IEEE Conference on Antenna Measurements and Applications (CAMA))
In this paper, the influence of the environment on an inductive location system is analyzed. In the inductive location method, high frequency magnetic fields generated by planar coils lead to induction in other coils, which is used for localization analysis. Magnetic fields are not affected by changes in the dielectric properties of the environment, which is an advantage over other localization methods. However, electrical material parameters can still affect the localization results by indirect effects. For this reason, in this publication the influence will be investigated using real material parameters and their effects on the localization will be considered, so that the robustness and the limits of the inductive localization can be evaluated.
Keywords: Planar coils; inductive locating; magnetic fields; environmental influences; eddy currents; tet_topic_hf

Will do? Causes and volitions - Wells, Aaron (Metascience)
Keywords: History and Philosophy of Science; General Social Sciences; History

Thematic Working Group 8 - Pedagogical Reasoning and Reflective Practice: Teacher's Professional Learning and Development (TLPD) in New Digital Realities - Drossel, Kerstin; Friesen, S.; Phillips, M.; Forkosh, A.; Christensen, R.; Trevisan, O.; Shaffer, D.W.; Horikoshi, I. (Moving forward to new educational realities in the digital era. Report of EDUsummIT 2023)

Der Einfluss von Verkäuferbewertungen auf die Kaufentscheidung - Ein systematischer Literaturüberblick - Krocker, Thomas

Eine empirische Untersuchung von Business-to-Business Online Bewertungen - Müller, Tobias Sören

Greta’s Gonna Wake Them Up? – An Empirical Analysis of the Im-pact of Greta Thunberg’s Global Climate Strike on Donations for Environmental Charitable Crowdfunding Campaings - Okumus, Hasan

Deutsch für den Beruf [Sammelrezension] Sander, Isa-Lou; Efing, Christian (Hrsg.): Der Betrieb als Sprachlernort. Tübingen: Narr Francke Attempto, 2021 (Kommunizieren im Beruf, 4). -- ISBN 978-3-8233-8442-7. 264 Seiten, € 68,00. Tichy, Ellen; Tesch, Felicitas (Hrsg.): Deutsch in Fach und Beruf. Aktuelle Fragen und neue Ansätze der Fremdsprachenvermittlung. Berlin: Peter Lang, 2021 (Berufssprache Deutsch in Theorie und Praxis, 2). -- ISBN 978-3-631-79553-8. 194 Seiten, € 49,95. Niederhaus, Constanze: Deutsch für den Beruf. Eine Einführung. Berlin: Erich Schmidt, 2022 (Grundlagen Deutsch als Fremd- und Zweitsprache, 4). -- ISBN 978-3-503-20545-5. 265 Seiten, € 22,00. - Prikoszovits, Matthias (Informationen Deutsch als Fremdsprache)
Keywords: General Medicine